Asuhan Keperawatan Pada Ny R P1A0 Post Sectio Caesarea Dengan Indikasi Preeklampsia Berat (PEB) Di Ruang Mawar RSUD Surakarta - Novitasari, Dyah Ayu; , Sulastri, S.Kp., M.Kes (2015)
NURSING IN NY. R P1A0 POST WITH INDICATION SECTIO CAESAREA SEVERE PREECLAMPSIA (PEB) IN THE ROSE HOSPITAL SURAKARTA (Dyah Ayu Novitasari, 2015, 87 pages) ABSTRACT Background: Sectio caesare often found in hospital with one of them that causes preeclampsia, pregnancy-specific multiorgan yaitukelainan characterized by the occurrence of hypertension, edema, and proteinuria but did not show signs of vascular abnormalities or previous hypertension, whereas the symptoms appear after the age of pregnancy 20 weeks. Objective: To determine the client's nursing care on post sectio caesarea with preekalmpsia indications include assessment, intervention, implementation, and evaluation of nursing. Results: After 3x24-hour nursing care for the results obtained, the client pain scale decreased from 7 to 3, the patient was able to mobilize the right and left oblique, patients already understand about baby care. Conclusion: Cooperation between the health care team with the client / family is indispensable for the success of nursing care, therapeutic communication can encourage more cooperative clients, so the problem of nursing patients about pain, mobilization barriers, and lack of knowledge can be implemented in accordance with the intervention of good and most problems can be solved. Keywords: sectio caesarea, severe preeclampsia, acute pain, barriers mobilization, lack of knowledge